The Effect of Financial Literacy on the Online Loan Users’ Behavior (Danabijak) through Financial Attitude as an Intervening Variable - Purnama sari, Syara; Sanusi, Anuar; Fionita, Ita (FEB - Universitas Lampung, 2023)
The presence of Fintech in Indonesia is a warning to conventional institutions included in the financial sector. If the conventional institutions are not able to keep following of growths, the tasks and responsibilities undertaken can be switched. It is because Fintech can provide the services with ease and minimize costs than the services of existing institutions. The purpose of this study was analyzed the effect of financial literacy on the online loan users’ behavior through financial attitudes as an intervening variable. The method of this study used associative method. The data analysis techniques used Smart Partial Least Square (PLS, 3.0). This research used Snowball Sampling Technique. The total of sample respondent was 100 respondents. The results of this study showed that financial literacy had a significant effect on the online loan users’ behavior, financial attitudes significantly influenced the online loan users’ behavior Danabijak. Meanwhile, the financial literacy had no significant effect on financial attitudes. Financial attitude was able to be intervening between financial literacy variables and Danabijak online loan user behavior variables.